PENGARUH PENGGUNAAN MEDIA POWERPOINT INTERAKTIF TERHADAP HASIL BELAJAR IPAS MATERI EKOSISTEM PESERTA DIDIK KELAS V SD NEGERI NAIKOTEN 1 - Kamelia Pracita Ere; Antonius Suban Hali; Daniel Williams Fointuna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is a quantitative research aimed at determining the effect of using interactive PowerPoint as a learning media on students’ learning outcomes in science (IPAS) on the ecosystem topic in class VD of SD Negeri Naikoten 1. This research employed a Pre-Experimental Design with a One Group Pre test Post test Design. The population and sample of this study consisted of 28 students of class VD SD Negeri Naikoten 1 in the 2025/2026 academic year. The sampling technique used was simple random sampling. Data collection techniques included tests and documentation, with instruments in the form of pretest and posttest consisting of 10 multiple-choice questions that had been validated by experts. The reliability test using Cronbach’s Alpha showed a value of 0.708, which is categorized as high reliability. The results showed that the pretest and posttest data were normally distributed with significance values of 0.119 and 0.123 (> 0.05), and homogeneous with a significance value of 0.910 (> 0.05). The hypothesis testing using the Paired Sample T-Test showed a significance (2-tailed) value of 0.000 (< 0.05), indicating a significant difference between students’ learning outcomes before and after the treatment. The mean score increased from 58.93 in the pretest to 77.50 in the posttest. Furthermore, the effect size calculated using Cohen’s d was 2.855, which falls into the very large category. Therefore, it can be concluded that the use of interactive PowerPoint as a learning media has a significant and highly effective impact on improving students’ learning outcomes.